2017
DOI: 10.1123/tsp.2016-0087
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Elite Rowers’ Challenge and Threat Appraisals of Pressure Situations: A Season-Long Observational Study

Abstract: Challenge cognitive appraisals are associated with superior performance compared with threat (Jones, Meijen, McCarthy, & Sheffield, 2009). However, research has not examined longitudinal temporal patterns of challenge and threat appraisals. In this study, 14 (five female) elite rowers (Mage = 25.79 years, SD = 2.67) provided self-reported appraisals data at four time points (baseline; before national trials; before the second world rowing cup regatta; and before the world rowing championships). The rowers’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Appraisals are instrumental in the stress process and can provide insight into how a performer responds, and subsequently adapts, to stressors in their sport. In contrast to extant literature (Cumming et al, 2017), the present study found that in the build-up to competition challenge appraisals significantly decreased. As organizational stressors (e.g., logistics and operations) typically relate to environmental factors often out of an athlete’s control (i.e., controlled by the coach or organization), it is likely that athletes felt a lack of control and subsequent mastery of events, particularly close to competition which led to reductions in challenge appraisals.…”
Section: Discussioncontrasting
confidence: 99%
“…Appraisals are instrumental in the stress process and can provide insight into how a performer responds, and subsequently adapts, to stressors in their sport. In contrast to extant literature (Cumming et al, 2017), the present study found that in the build-up to competition challenge appraisals significantly decreased. As organizational stressors (e.g., logistics and operations) typically relate to environmental factors often out of an athlete’s control (i.e., controlled by the coach or organization), it is likely that athletes felt a lack of control and subsequent mastery of events, particularly close to competition which led to reductions in challenge appraisals.…”
Section: Discussioncontrasting
confidence: 99%
“…A more promising predisposition that is nested within challenge and threat theory is the notion of trait challenge and threat. Contemporary research with elite rowers (Cumming et al, 2017) shows that predisposed cognitive appraisal style is associated with, and further predicts, subsequent state cognitive appraisals. Specifically, predisposed challenge was associated with eventspecific state challenge, and predisposed threat was associated with event-specific state threat, on approach to subsequent motivated performance situations.…”
Section: Predispositionsmentioning
confidence: 99%
“…This added level of detail would have been optimal for assessing not only anxiety but also whether self-reported arousal was characteristic of challenge or threat states. In a very recent study, Cumming, Turner, and Jones (2017) have broken new ground by measuring self-reported challenge and threat appraisal with elite rowers over an entire season, and have called on researchers to measure longitudinally but with the physiological measures as well. Taking state anxiety measurements over multiple time periods would have built a more accurate picture of the athletes in this study, compared to the single measure of trait anxiety.…”
Section: Methodological Issuesmentioning
confidence: 99%